THE IMPLEMENTATION OF THE HEAD ELECTION FOR THE HEAD OF THE VILLAGE OF KASANG LIMAU SUNDAI, KUANTAN HILIR SEBERANG DISTRICTS KUANTAN SINGINGI DISTRICT IN 2018 - Uci Purnama Sari; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT This study aims to find out how the of implementation the Kasang Limau Sundai Village Head Election, Kuantan Hilir Seberang District, Kuantan Singingi Regency in 2018. This type of research is descriptive and the approach in this study is qualitative. Data collection was obtained through interviews and documentation. This research was conducted in Kuantan Singingi Regency. The results of this study indicate that the of implementing the Kasang Limau Sundai village Head Eelection is Based on the Kuantan singing Regent Regulation Number 55 of 2018 concerning the implementation of simultaneous Village Head Election. The basis is very importantbecause the process in selecting the village head is interrelated, is for the stages in the village head election .The first is the preparation stage for the final notification of the election, the position of the village head submitted by the BPD, the formation of the Election Committee is directly elected by the BPD. Secon, in the nomination stage, the election Committee re-assures the is completeness and validity of the nomination administration for each prospective village head. The accurrence of Money politics which is considered normal by the public, before H’s heart, the voting is usually carried out, the success team from each candidate will use various ways to attract the sympathy of the public, some openly distribute basic necessities to others, thre are also those who distribution cash ( dawn attack), in the election of head of state. village are often inseparable from the use of money as an effort to attract community sympathy. Third Stage of the voting the election committee has provided 1 TPS. The voting went smoothly. Even thoug there are voters who cannot come to the polls directly to vote. The election ccommitte went directly to visit the homes of elderly voters so thet they could still exercise their right to voters who voted using cigarette butts. Fourth stage of determining the elected village Head was inaugeurated directly by the Regent of Kuantan Singingi Regency. Keywoard : implementating, Village Head Election, Democracy